A KNOWLEDGE BASED METHODOLOGY TO UNDERSTAND THE USER BROWSING BEHAVIOR FOR QUALITY MEASUREMENT OF THE WEBSITES USING WEB USAGE MINING (International Journal of Engineering and Computer Science, 2013)
World Wide Web is a huge repository of web pages and links. It provides huge information for the Internet users. The growth of web is tremendous as approximately one million pages are added daily. Users’ accesses are recorded in web logs. Because of the tremendous usage of web, the web log files are growing at a faster rate and the size is becoming huge. Web data mining is the application of data mining techniques. Extraction of user behavior is an important work in Web Mining. Web Usage Mining applies mining techniques in log data to extract the behavior of users. Today most of the banks are entered in the web world. They are launching various online facilities day to day for customers. This paper presents the browsing behavior of the user in banks websites and the quality measurement factors of the website. In this study we have analyzed log server of three major public sector banks i.e. State Bank of India, Bank of Maharashtra and Bank of Baroda and three major private sector banks i.e. ICICI bank, HDFC bank and Federal bank. The obtained results can be used in different applications like, site modifications, business intelligence, system improvement, and web personalization and useful to tell, how to provide customer with more exactly needed and accurate on line information to improve banking activities and achieve business goal.